Borowiczek . Borovichok - Łukianczikow, Siergiej (Eureka Media, 2007)
Verzio FF Submission Andriej is a boy from a Belarusian village, who was born with numerous physical and psychic defects. For many years his parents were unable to decide whether to bring him up themselves or send him to an orphanage. The relationship between Andriej and his family, especially with his mother and one of his brothers, were by no means easy to start with. They had to dedicate a lot of time and patience to learning how to communicate with Andriej and persuading him to communicate with them. Their efforts soon brought Andrej much closer to his family.